THE EFFECT OF JIGSAW TECHNIQUE AND STUDENTS’ VOCABULARY MASTERY ON READING COMPREHENSION OF THE EIGHTH GRADE STUDENTS OF SMPN 4 SINGARAJA - Pariati, Ni Nengah (Yavana Bhasha : Journal of English Language Education, 2018)
The aim of this study was to investigate the effect of Jigsaw technique and students’vocabulary mastery on reading comprehension of the eighth-grade students of SMPN 4Singaraja. This study was a quasi-experimental study with Posttest-Only Control GroupDesign by 2x2 factorial arrangement which involved a sample of 80 students. The data werecollected by using vocabulary and reading comprehension test then analyzed by Two-wayANOVAand Tukey test. The result indicates that (1) there was a significant effectonreadingcomprehension between the students who were taught using the Jigsaw technique andthose who were taught by using conventional, (2) there was a significant effect of theinteraction between the implementation of teaching techniques and students’ vocabularymastery on reading comprehension, (3) there was a significant effect in readingcomprehension between the students with high vocabulary mastery who were taught byusing Jigsaw technique and those who were taught by using conventional technique, (4)there was a significant effect in reading comprehension between the students with lowvocabulary mastery who were taught by using Jigsaw technique and those who weretaught by using conventional. The result of the research showed that the Jigsaw techniquewas more effective for teaching reading comprehension than conventional.